Thermal effects in reactive liquid chromatography - Sainio, Tuomo; Kaspereit, Malte; Kienle, Achim; Seidel-Morgenstern, Andreas (Chemical Engineering Science, 2007)
Thermal effects in unsteady-state liquid phase chromatographic reactors were investigated experimentally in a thermally insulated column. In the case of an exothermic esterification reaction catalyzed by an acidic ion-exchange resin, a self-amplifying positive thermal wave was found to develop in the reactor. This improved the reactor performance considerably when compared to isothermal conditions: both conversion of reactants and the mole ratio of the desired and undesired products in a product fraction increased. The heat of reaction, enthalpy of adsorption, and heat of mixing all contribute to the thermal behavior of the reactor. The coupling between the concentration fronts and thermal waves was elucidated by means of numerical simulations. The solid phase to fluid phase heat capacity ratio was found to be an important parameter because it affects the magnitude and propagation velocities of the thermal waves. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Chromatographic reactor; Esterification; Ion-exchange resin; Non-isothermal reactor; Process intensification; Thermal effects